The Clustered Olfactory Receptor Gene Family 262: Genomic Organization, Promotor Elements, and Interacting Transcription Factors - Hoppe, Reiner; Frank, Henning; Breer, Heinz; Strotmann, Jörg (Genome Research, 2003)
For six mouse olfactory receptor genes from family 262 which are expressed in clustered populations of olfactory sensory neurons, the genomic as well as cDNA structures were deciphered. All genes contained several exons which in some cases were alternatively spliced. Immediately upstream of the transcription start sites, sequence motif blocks were identified that are highly conserved among olfactory receptor (OR) genes which are expressed in clustered neuronal populations. By means of electrophoretic mobility shift assays, it was demonstrated that segments of the motif block region interact with proteins extracted from nuclear fractions of the olfactory epithelium. Yeast one-hybrid screenings of an olfactory cDNA library led to the identification of a set of transcription factors that specifically bind to particular elements of the motif block region. The identified factors can be categorized into two types: One group is known to be involved in transcriptional initiation, and the second group represents factors involved in pattern formations. The identified components may contribute to govern the precise topographic expression pattern of olfactory receptor genes.